Intention to use mobile health in antenatal care service: Among primary health care unit workers, Bench-Sheko zone, southwest Ethiopia. - Shimeles Wondimu; Mohamed J Abawari; Yohannes Kebede (PLOS Digital Health)
The use of mobile health (mHealth) technology has the potential to enhance maternal and child health care, particularly in low-income countries. However, evidence regarding its practicality and effectiveness remains limited. In Ethiopia, research on health workers' intention to adopt mHealth technology for maternal health services is notably scarce, emphasizing the need for thoughtful evaluation and further studies to explore its real-world application. This study aims to assess the intention of primary health care unit workers towards using mobile health technology in antenatal care services in Bench-Sheko Zone, Southwest Ethiopia. A cross-sectional study was conducted from June 27, 2023, to July 27, 2023. Data were collected from 316 primary health care unit workers using a simple random sampling technique. SPSS version 25 was used for data analysis, including multivariable linear regression modeling. The response rate was 98.7%. The mean age of participants was 29.2 years, and the mean score for behavioral intention to use mobile technology in ANC services was 65%. Predictors included perceived mobile self-efficacy (β=0.318, p<0.001), perceived compatibility (β=0.601, p<0.001), mobile ownership (β=1.173, p=0.041), eHealth training (β=0.768, p=0.008), and mobile use experience (β=0.176, p<0.001). Local health managers should facilitate training to boost health workers' mobile self-efficacy, and policymakers should consider the compatibility of mHealth technology with existing practices.